Comparative analysis of adherence to rules and regulations in public and religious schools in Sabang City - Maimun; Oktaviani, Alfi; Hayati, Erna (Journal of Education, Linguistics, Literature, and Art, 2023)
Education is a process of changing the behavior of students, meanwhile, school is a vehicle for developing the behavior of students who have not been able to play its role optimally. This study aims to determine the differences in obedience to the rules between SMA Negeri 1 Sabang dan MAN Sabang, to find out the factors that form student obedience to the rules in SMA Negeri 1 Sabang and MAN Sabang. This study uses a mix methods research that combines quantitative and qualitative research. The results showed that (1) there were differences in student obedience to dicipline between public schools an religious schools with a sig value of 0,029 < 0,05. (2) the factors that form student obedience to discipline are influenced by two factors, namely internal factor and external factors and with the support of school and community environmental factors.